2011
DOI: 10.1063/1.3545982
|View full text |Cite|
|
Sign up to set email alerts
|

Protein folding in a reverse micelle environment: The role of confinement and dehydration

Abstract: Characterization of the molecular interactions that stabilize the folded state of proteins including hydrogen bond formation, solvation, molecular crowding, and interaction with membrane environments is a fundamental goal of theoretical biophysics. Inspired by recent experimental studies by Gai and co-workers, we have used molecular dynamics simulations to explore the structure and dynamics of the alanine-rich AKA 2 peptide in bulk solution and in a reverse micelle environment. The simulated structure of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
6
19
0
Order By: Relevance
“…19 Our previous computational studies of RM confined peptides followed earlier work by Mukherjee et al 17,18 in which the secondary structure stability of monomers of the 19-residue, alanine-rich AKA 2 peptide in spherically restrained and unrestrained AOT RMs and in bulk water was analyzed. 34 In agreement with experiment, these studies showed increased helical content for peptides in RMs as compared to bulk water. They also revealed that the shape of the simulated RMs fluctuated significantly allowing the peptides to interact with the AOT surfactant molecules in addition to the core water molecules.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…19 Our previous computational studies of RM confined peptides followed earlier work by Mukherjee et al 17,18 in which the secondary structure stability of monomers of the 19-residue, alanine-rich AKA 2 peptide in spherically restrained and unrestrained AOT RMs and in bulk water was analyzed. 34 In agreement with experiment, these studies showed increased helical content for peptides in RMs as compared to bulk water. They also revealed that the shape of the simulated RMs fluctuated significantly allowing the peptides to interact with the AOT surfactant molecules in addition to the core water molecules.…”
Section: Introductionsupporting
confidence: 75%
“…34,35,49,50 For our simulations of Aβ 16−22 in AOT RMs, Figure 2 shows the average number of molecules (AOT head groups, AOT tail groups, and sodium ions) within 4 Å of each amino acid side chain of the monomers and dimers, respectively. The number of interactions for the peptides does not change significantly between the monomer and dimer systems, and in both systems there are significant hydrophobic interactions between the V 18 FFA 21 of the Aβ 16−22 peptides and the AOT tail groups.…”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38] There are several pioneering experimental and computational studies relating the aggregation properties to the conformations adopted by Aβ peptides upon their interaction with lipids. [39][40][41][42][43][44][45][46][47][48][49][50][51][52] The aggregation process depends on the type of lipids (i.e., neutral or charged), peptide and salt concentrations, and pH. It has been reported that charged lipids induce β-strand structure in Aβ peptides to a similar extent as the increase in their concentration in solution, and that CD spectroscopy measurements can evidence significant (i.e., about 40-60%) β-strand content.…”
Section: Introductionmentioning
confidence: 96%
“…3 These properties make RMs powerful tools in which to probe confinement effects and dehydration on biological molecules. 46 …”
Section: Introductionmentioning
confidence: 99%